2019
DOI: 10.1016/j.clinph.2019.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal motor events in epilepsy: Is there a defined physiological network?

Abstract: Highlights 1. Nocturnal movements have consistent power changes in a physiological network. 2. Nocturnal movements can be influenced by epilepsy, increasing the frequency and magnitude of events. 3. Similarities in first clinical sign and movement semiology may suggest onset within the network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Case series have been published for Australian SEEG patients, but these were not aimed primarily at reporting complication rates. [29][30][31][32] Importantly, SEEG is relatively new in Australia, being introduced only 10 years ago. The present study suggests that despite the relative inexperience when compared with European centres, overall, the complication rates and EZ localisation rates were comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case series have been published for Australian SEEG patients, but these were not aimed primarily at reporting complication rates. [29][30][31][32] Importantly, SEEG is relatively new in Australia, being introduced only 10 years ago. The present study suggests that despite the relative inexperience when compared with European centres, overall, the complication rates and EZ localisation rates were comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigating SEEG have previously reported data from Australia. Case series have been published for Australian SEEG patients, but these were not aimed primarily at reporting complication rates 29–32 . Importantly, SEEG is relatively new in Australia, being introduced only 10 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…50 Example movements include head banging, head rolling, body rocking, body rolling, and leg banging. 64 The movements usually have frequency of 0.5 Hz to 2 Hz and can be associated with humming or other inarticulate sounds. Compared with epileptic events, environmental disturbance, including being spoken to, may result in cessation of the movements.…”
Section: Epilepsy Versus Select Sleep-related Movement Disordersmentioning
confidence: 99%